Implementasi Pembelajaran Data Analytics dan Software Development PT Revolusi Cita Edukasi - Putra, Dennys Pranata; Wijaya, Novia (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Digital transformation and technological advancements have increased the demand for highly qualified workers. Higher education institutions play a crucial role in producing graduates who are competitive in the industry. The community service program organized by Kemendikbudristek aims to enhance graduates' competencies through real work experiences and the development of both hardskills and softskills. PT Revolusi Cita Edukasi (RevoU) partners in this program, providing intensive training in data analytics and software development. The program involves students in real-world projects, such as a capstone project that includes analyzing sales data from vending machines and developing an interactive dashboard. The final result is an interactive dashboard that provides essential business insights related to vending machine sales. This dashboard assists stakeholders in making better decisions based on accurate data. The quality of the results is measured by the dashboard's ability to present real-time data and its usability. Recommendations for program improvement include implementing a peer assessment system, regular monitoring by section managers, enhancing mentor roles, and providing additional learning resources. The program is expected to continue evolving and have a greater positive impact on participants' career and skill development in the future.